The Factors Factors Affecting The Productivity Of Oil Palm Harvester Employees at PT Agromuko Tanah Rekah Estate - M.Fadhlullah Prasetyo Zizou Aly; Bambang Sumantri; Indra Cahyadinata (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to evaluate the productivity level of oil palm harvesters at PT. Agromuko Tanah Rekah Estate Plantation and identify the factors that influence it. Methodology: The approach used in this study is multiple linear regression analysis with the help of SPSS version 20 software. The sampling technique applied is simple random sampling, with a total sample of 192 harvesters, from which 66 respondents were selected. The location of the study was determined intentionally using the purposive sampling method. Results: The results showed that the productivity of oil palm harvesters at PT. Agromuko Tanah Rekah Estate is relatively high, reaching 140 kilograms/hour. The variables of age, number of family dependents, attendance rate, and incentives were proven to have a significant influence on the productivity level of harvesters. Findings: Age, number of family dependents, attendance rate, and incentives were found to have a significant influence on the productivity level of harvester workers. Conclusion: The productivity of oil palm harvesting workers at PT Agromuko Tanah Rekah Estate is considered very good, variables that affect the productivity of oil palm harvesting workers include employee age, family dependents, attendance, and incentives provided to increase their productivity at PT Agromuko Tanah Rekah Estate. Type of Paper: Empirical Research Paper.